CD90 determined two subpopulations of glioma-associated mesenchymal stem cells with different roles in tumour progression. Issue 11 (November 2018) - Zhang, Qing; Yi, Dong-Ye; Xue, Bing-Zhou; Wen, Wan-Wan; Lu, Yin-Ping; Abdelmaksou, Ahmed; Sun, Min-xuan; Yuan, De-tian; Zhao, Hong-Yang; Xiong, Nan-Xiang; Xiang, Wei; Fu, Peng
Abstract Human glioma-associated mesenchymal stem cells (gbMSCs) are the stromal cell components that contribute to the tumourigenesis of malignant gliomas. Recent studies have shown that gbMSCs consist of two distinct subpopulations (CD90+ and CD90− gbMSCs). However, the different roles in glioma progression have not been expounded. In this study, we found that the different roles of gbMSCs in glioma progression were associated with CD90 expression. CD90high gbMSCs significantly drove glioma progression mainly by increasing proliferation, migration and adhesion, where as CD90low gbMSCs contributed to glioma progression chiefly through the transition to pericytes and stimulation of vascular formation via vascular endothelial cells. Furthermore, discrepancies in long non-coding RNAs and mRNAs expression were verified in these two gbMSC subpopulations, and the potential underlying molecular mechanism was discussed. Our data confirm for the first time that CD90high and CD90low gbMSCs play different roles in human glioma progression. These results provide new insights into the possible future use of strategies targeting gbMSC subpopulations in glioma patients.